Dissection of the epoxyjanthitrem pathway in Epichloë sp. LpTG-3 strain AR37 by CRISPR gene editing - Miller, Taryn A.; Hudson, Debbie A.; Johnson, Richard D.; Singh, Jaspreet S.; Mace, Wade J.; Forester, Natasha T.; Maclean, Paul H.; Voisey, Christine R.; Johnson, Linda J. (Frontiers in Fungal Biology, 2022)
Epichloë festucae var. lolii and Epichloë sp. LpTG-3 are filamentous fungal endophytes of perennial ryegrass (Lolium perenne) that have a substantial impact on New Zealand’s agricultural economy by conferring biotic advantages to the host grass. Overall, Epichloë endophytes contribute NZ200 million to the economy annually, with strain AR37 estimated to contribute NZ3.6 billion to the New Zealand economy over a 20-year period. This strain produces secondary metabolites, including epoxyjanthitrems, which are a class of indole diterpenes, associated with the observed effects of AR37 on livestock and insect pests. Until very recently, AR37 was intractable to genetic modification but this has changed with the application of CRISPR-Cas9 based gene editing techniques. In this paper, gene inactivation by CRISPR-Cas9 was used to deconvolute the genetic basis for epoxyjanthitrem biosynthesis, including creating an AR37 strain that has been edited to remove the biosynthesis of all indole diterpenes. We show that gene editing of Epichloë can be achieved without off-target events or introduction of foreign DNA (footprint-less) through an AMA1-based plasmid that simultaneously expresses the CRISPR-Cas9 system and selectable marker. Genetic modification events in these transformants were investigated through genome sequencing and in planta chemistry.